2008
DOI: 10.1016/j.socscimed.2008.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Church ladies, good girls, and locas: Stigma and the intersection of gender, ethnicity, mental illness, and sexuality in relation to HIV risk

Abstract: Inner city women with severe mental illness may carry multiple stigmatized statuses. In some contexts these include having a mental illness, being a member of an ethnic minority group, being an immigrant, being poor, and being a woman who does not live up to gendered expectations. These potentially stigmatizing identities influence both the way women's sexuality is viewed and their risk for HIV infection. This qualitative study applies the concept of intersectionality to facilitate understanding of how these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 20 publications
2
100
0
1
Order By: Relevance
“…When cases were gender-typical, participants expressed less sympathy and decreased willingness to provide help or support, relative to cases perceived as gender-atypical. In the context of applied scholarship, Collins and colleagues Collins, von Unger, & Armbrister, 2008) have unpacked relationships between gender, ethnicity, serious mental illness, and HIV/AIDS risk behaviors. They found complex interplay among identities (particularly gender and mental illness), the social norms affecting these identities, and sexual risk-taking.…”
Section: Double Stigma and Intersectionalitymentioning
confidence: 99%
“…When cases were gender-typical, participants expressed less sympathy and decreased willingness to provide help or support, relative to cases perceived as gender-atypical. In the context of applied scholarship, Collins and colleagues Collins, von Unger, & Armbrister, 2008) have unpacked relationships between gender, ethnicity, serious mental illness, and HIV/AIDS risk behaviors. They found complex interplay among identities (particularly gender and mental illness), the social norms affecting these identities, and sexual risk-taking.…”
Section: Double Stigma and Intersectionalitymentioning
confidence: 99%
“…In investigations of stigma and prejudice focused on a particular population there is a powerful drive to identify commonalities in this experience (Crenshaw, 1996). The paper by Collins, von Unger, and Armbrister (2008) analyzes Latina women's experience of mental illness stigma within the context of their sexuality, gender and ethnicity. They find that mentally ill women describe a range of negative experiences, such as sexual health risks, that cannot be reduced to their mental illness per say, but to the intersection of these multiple stigmatized identities.…”
Section: Bridging Stigma and Prejudice Research Traditionsmentioning
confidence: 99%
“…This strategy consists in projecting the image of a woman closely tied to religious values to facilitate a protective effect against risky behavior based on discrimination (Collins, Von Unger & Armbrister, 2008). Another study made with Latina women living in the United States found that religious and spiritual beliefs had a positive influence in reducing risky behavior by providing them with a certain structure of everyday control and prevention when facing the typical disorganization and impulsiveness of people with SMI (Loue & Sajatovic, 2006).…”
Section: Effects Of Social Stigmamentioning
confidence: 99%
“…Most of the epidemiological studies of risk factors associated with HIV prevalence in people with SMI have focused on individual factors or those inherent to a person's characteristics, but very few have looked into the sociocultural factors conditioning sexual behavior and prevention practices (Carey, Carey, Weinhardt & Gordon, 1997;Collins, Von Unger & Armbrister, 2008;Coverdale, Shotte, Ruiz, Pharies & Bayer, 1994;Loue & Sajatovic, 2006;Pinto, Mann, Wainberg, Mattos & Oliveria, 2007). These factors are deemed to be implied, are beyond a person's control and reduce his/her ability to avoid risk, such as social exclusion for human rights' violation Stevenson & Eilers, 1992;Taylor, 2007), poor quality and coverage of health services, and social stigma of illness, among others (Collins, 2001;Kloos et al, 2005).…”
Section: Introductionmentioning
confidence: 99%